Analysis of the Pretension Angle of Mooring Lines SPM and Its Effect on the Tension and Strength of Subsea Marine Hose - Rabiatul Muthi’ah; Murdjito Murdjito; Eko Budi Djatmiko (International Journal of Offshore and Coastal Engineering, 2025)
The industry of oil and gas industry have developed along with advances in technology, so does the mooring system. Mooring system is a series that functions to keep the ship station or floating platform at all water depths. Currently, there are many types of moorings that can be used, one of which is Single Point Mooring (SPM). SPM itself consists of various types of mooring legs, as well as other supporting components such as subsea hose or riser. Subsea hose and mooring lines are closely related because in the application, the length of the mooring lines also determines the offset or limitation of motion of the SPM, while the subsea hose also has a maximum limit of pull caused by the movement of the SPM. In addition to the length of the mooring lines, another factor is the pretension angle. Therefore, in this study, an analysis was carried out by varying the pretension angle (45°, 50°, 55°, 60°) under extreme conditions and inline loading by reviewing the tensile forces on the mooring lines and risers. The larger the angle, the smaller the tensile force, so the offset would be larger, and vice versa. The results of this study indicate that the pretension angle applied must be appropriate so that the tensile force on the mooring lines that occurs can also be appropriate.